Sociodemographic Characteristics and Length of Imprisonment As Institutional Exposure: A Quantitative Study In The Perspective of Applied Psychology in Detention - Muhammad Zulfan Azmi; Lutfi Faishol (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Detention houses are closed institutional environments characterized by restrictions on freedom and strict social structures, thereby forming a unique context for psychosocial experiences among inmates. In the study of social and applied psychology, individual characteristics and duration of institutional exposure are seen as important factors for understanding the experience of detention more comprehensively. This study aims to analyze the relationship between sociodemographic characteristics and the length of imprisonment of inmates as a form of institutional exposure in the Banyumas State Prison. This study uses a quantitative approach with a secondary data analysis design. The study participants were the entire population of inmates who were administratively recorded during the study period. The data analyzed included sociodemographic characteristics and criminal duration. Data analysis was conducted using both descriptive statistics and inferential statistics, including chi-square tests. The results showed variation in the length of time of the sentence based on specific sociodemographic characteristics, although not all relationships reached statistical significance. These findings suggest that the distribution of criminal length is not random and cannot be explained by a single individual characteristic. This study highlights the significance of social psychology and applied psychology perspectives in interpreting institutional administrative data within the context of detention exposure, and serves as a basis for further research that integrates direct psychological measurements to gain a deeper understanding of institutional impacts.